A study on the customer perceptions toward ladies department Mun Loong Hankyu Jaya Bangsar / Ahmad Faiezal Mohamed Nazar - Mohamed Nazar, Ahmad Faiezal (1998)
Retailing in Malaysia has been growing tremendously over the last few years. The competition among the retailers is getting fiercer. And nowadays cause of the economic slow down there must have careful operations and retailer will find it more important than ever to develop new and clear direction to maintain their share market. Lifestyle marketing, competitive pricing, store ambience and displays, excellent customer service and right merchandising blend are just some areas retailers have to seriously consider in the present years. Nowadays, retailers need to stay close to the customers and understand their changing tastes, preferences, perception and expectations. Since now we are in economic slow down so the purchasing power of the customers also decrease. So as a retailer we should seen clearly what the customers needs and wants at this time not at the point of retailers. This study on the customers perceptions towards Ladies Wear Department, MHJ Bangsar is prepared to determine the customers perception towards the department product arrangement, displays, decoration, environment, product prices, assortment, quality, services and facilities and also the sale assistants. The objective of the study is to measure up the customer's perceptions and expectations towards this department.